Networking for training Level 3/4 biosafety laboratory staff - Huang, Yi (J Biosaf Biosecur, 2019)
Worldwide, public health systems are continually challenged by emerging and re-emerging viruses. It is therefore important that high-containment labs coordinate and communicate globally to share their experiences and lessons to improve their capacity to respond to threats. The National Biosafety (Level 4) Laboratory in Wuhan, CAS, which is the first Level 4 biosafety laboratory (BSL-4) in China, has been certified recently and it is expected to play an important role in the prevention and control of highly infectious agents in future. Trained and experienced staff in such organizations is the most important factor contributing to safety and security. Therefore, it is imperative to develop a standard training program. Accordingly, in the present study, we developed an improved training program and assessment system based on policies and practices developed by BSL-3/4s in other countries. It included the following three components: (1) A flexible modularized theoretical training: This training comprised 14 modularized theoretical topics such that staffs with different backgrounds could take this theoretical training with different topic combinations according to their knowledge and skill levels; (2) A standardized practical training assessment: This comprehensive assessment, which could be used with biosafety laboratory staff before, during, and after training, included standard operation procedures to meet the special requirements of trainees with different scores; and (3) An applicable documentation system: A certification system was established to evaluate the ability of all staff working inside or outside the laboratory, implemented by a special committee. This certification was approved and authorized by the director of the laboratory and was classified into three grades with corresponding minimal requirements. Further, the present study examined the importance of and need for networking for training BSL-3/4 staff. The establishment of rigorous standards for training BSL-3/4 staff will instill confidence in the public, policy makers, and security officials. Additionally, the expanded international network of BSL-3/4s will continue to be operated safely and will pose no risk to scientific staff, local communities, surrounding environment, and host nations. The clarification and coordination of training standards will help develop a highly-qualified biocontainment workforce and will result in a series of programs that will enable scientists to develop measures to deal with existing threat agents and new diseases that emerge.